Healthy Human Laryngopharyngeal Sensory Innervation Density Correlates with Age. (16th July 2022) - Cole, Caroline L.; Yu, Victoria X.; Perry, Sarah; Seenauth, Anisa; Lumpkin, Ellen A.; Troche, Michelle S.; Pitman, Michael J.; Moayedi, Yalda
Abstract : Objective: Somatosensory feedback from upper airway structures is essential for swallowing and airway defense but little is known about the identities and distributions of human upper airway neurons. Furthermore, whether sensory innervation modifies with aging is unknown. In this study, we quantify neuronal and chemosensory cell density in upper airway structures and correlate with age. Methods: Participants underwent biopsies from base of tongue, lateral and midline pharyngeal wall, epiglottis, and arytenoids (N = 25 13 female/12 male; 20–80 years, mean 51.4 years without clinical diagnosis of dysphagia or clinical indication for biopsy). Tissue sections were labeled with antibodies for all neurons, myelinated neurons, and chemosensory cells. Densities of lamina propria innervation, epithelial innervation, solitary chemosensory cells, and taste buds were calculated and correlated with age. Results: Arytenoid had the highest density of innervation and chemosensory cells across all measures compared to other sites. Taste buds were frequently observed in arytenoid and epiglottis. Base of tongue, lateral pharynx, and midline posterior pharynx had minimal innervation and few chemosensory cells. Epithelial innervation was present primarily in close proximity to chemosensory cells and taste buds. Overall innervation and myelinated fibers in the arytenoid lamina propria decline with aging. Conclusion: Findings establish the architecture of healthy adult sensory innervation and demonstrate the varied distribution of laryngopharyngeal innervation, necessary steps toward understanding the sensory basis for swallowing and airway defense. We also document age‐related decline in arytenoid innervation density. These findings suggest that sensory afferent denervation of the upper airway may be a contributing factor to presbyphagia. Level of Evidence: NA Laryngoscope, 133:773–784, 2023 Abstract : Somatosensory feedback from upper airway structures is essential for swallowing and airway defense but little is known about the identities and distributions of human upper airway sensory neurons, or if these structures are modified with age. In this study, we analyzed healthy human biopsies from five distinct anatomical regions of the upper airway for density of all neurons, myelinated putative mechanosensory neurons, and chemosensory structures using immunohistochemistry and densitometry. We describe the architecture of healthy adult sensory innervation and found age‐related decline in arytenoid innervation density, suggesting that sensory afferent denervation may contribute to presbyphagia.